Evaluación de calidad de agua del río Yanayacu ubicado en el cantón Salcedo provincia de Cotopaxi periodo 2021-2022. - Quishpe Quispe, Yajaira Selena (2022)
The research project had as purpose to assess the water quality for irrigation from Yanayacu River located into Salcedo canton, Cotopaxi province in the 2021-2022 period. For this, it was selected the three sampling points purpose, along the riverbed, through an exploration in the area, also, it is considered variables according to the research purpose, resource uses and activities near the river for the physicochemical and microbiological parameters identification, (arsenic, boron, fecal coliforms, EC conductivity, chromium, chemical oxygen demand COD, dissolved oxygen, potential hydrogen pH, sodium, total solids and temperature). For the sampling was used the methodology based on the regulations, what help the samples handling, conservation, preparation, filling, refrigeration, identification, transport and reception, for the dry season is performed three samples for each point and for wet season, only was made intake. The eight parameter results were compared with those set into Ministerial Agreement 0 97 A, Table 3, Water quality criteria for agricultural irrigation and Table 4 Parameters water quality levels for irrigation, which are found within the maximum permissible limits for the two seasons the year. For the simplified water quality index (ISQA) determination was used five physicochemical parameters into own equations established for the index determination, by getting as a result 52.8 for dry season and 48.99 for wet season, by being in the doubtful quality range, that is, contaminated water.